A Roadmap for European Universities Policy Recommendation to Achieve HEI Sustainability: The Case of INVEST EU Alliance - Ipsilandis, Pandelis; Kokkinos, Konstantinos; Samaras, Nicholas (European Scientific Journal, ESJ, 2024)
The European Union (EU) has emphasized the value of higher education, research, and innovation as engines for the continued socioeconomic and cultural advancement of Europe on several occasions. The European Universities Initiative (EUI), one of the most recent policy initiatives by the European Commission (EC) aims at advancing this agenda, via transnational collaborations of Higher Education Institutions (HEIs) to find new strategies for fostering European scientific excellence. This effort provides an administrative answer to the goals of European policy in terms of higher education, research, and innovation. This paper analyzes the potential benefits and risks the EUI alliances might face along four dimensions: their internal coordination, their methods of resolving conflicts, the commitment of member universities, and the cultural characteristics of the alliances. It is based on interviews with individuals holding key leadership and management roles in five member universities. We provide the case of INVEST EUI alliance as a complete case study for all the governmental, educational, structural, and financial challenges faced to draw a roadmap that can be used as policy recommendation for EU.